Hugo de Kempeneer - Hugo Ké : Made in Belgium, Biennale di Venezia 1980 Venice Biennial. - 39TH Biennale di Venezia 1980 (Venezia : La Biennale di Venezia, 1980)
His contribution to the 1980 Venice Biennial as shareholder of the Belgian arms' manufacturing company was a shooting gallery such as is normally to be seen at fairs, with one important exception. The folder contains a 5 in 100 scale reproduction of the gallery. The Belgian participation in this, the 39th Venice Biennial is being organized by the Art's promotion Office of the department of International Cultural Relations of the Ministry of Education and Flemish Culture.
korte biog. [1 p.]
La Biennale di Venezia 1980 : pav. België. La Biennale di Venezia. 1980-06-01. 1980-09-28
Engels & Italiaans
kunstcatalogus
Keywords: De Kempeneer, Hugo